Adaptive Dynamic Activity Mapping: a Novel Approach to Real-time Heatmap with YOLOv8 - Yuliawati, Nursiyanto; Yuliawati, Dona; Andriyadi, Anggi (INOVTEK Polbeng - Seri Informatika, 2025)
The implementation of QR Code technology at Youth Cafe aims to increase ordering efficiency and provide a more comfortable experience for customers. Each table is equipped with a unique QR code that can be scanned to access the menu and place orders via the mobile web-based application. This application was designed using Native PHP with MySQL as the database, to ensure stability and optimal performance. The success of the system is measured by increasing order time efficiency by up to 50%, reducing manual errors by 90%, and the system's ability to handle up to 500 orders per day without interruption.  Customer surveys show satisfaction levels increased by 35% after application implementation. These results show that the use of QR Code technology has succeeded in improving operations, efficiency and service quality at Youth Cafe, as well as making a significant contribution to innovation in the food and beverage industry.